Coping with the Crises: Historical Comparison on Responses to the Crises in the Extreme Salient of Java - Nawiyanto, Nawiyanto (TAWARIKH, 2013)
ABSTRACT: Did the peopleâs response to the crisis change over time? Using three different crisis experiences in the 1930s, the 1940s, and the late 1990s, the article will examine how the local society of Besuki (residency) in East Java, responding to them. The three crises put a strong blow to the livelihoods of the local people. But the adversity of the impact was unevenly felt by different groups of people, depending on the nature of their material bases and the availability of alternative sources of income. It finds that there were similarities in the peopleâs responses. During the three events, some sought to find a relief in agriculture, retail trade, and forest sectors, apart from making adjustments in expenditure and consumption patterns to mitigate the adverse consequences of the crises. But for those who found no other alternatives, the crises forced them to do illegal activities, including lootings, stealings, and illegal logging. Such adaptive responses seem to have been quite common. Crises also meant a higher number of crimes.KEY WORDS: Responses to crisis, Indonesian crises, historical comparison, and Besuki residency.About the Author: Dr. Nawiyanto is a Lecturer at the Department of History, Faculty of Letters UJ (University of Jember), Jalan Kalimantan No.37 Jember City 68121, East Java, Indonesia. He can be reached at: snawiyanto@gmail.comHow to cite this article? Nawiyanto. (2013). âCoping with the Crises: Historical Comparison on Responses to the Crises in the Extreme Salient of Javaâ in TAWARIKH: International Journal for Historical Studies, Vol.4(2) April, pp.129-150. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 4, 2013); Revised (March 6, 2013); and Published (April 28, 2013).